Protein expression and oxygen consumption rate of early postmortem mitochondria relate to meat tenderness. Issue 4 (1st April 2015) - Grabež, V.; Kathri, M.; Phung, V.; Moe, K. M.; Slinde, E.; Skaugen, M.; Saarem, K.; Egelandsdal, B.
Abstract: Oxygen consumption rate (OCR) of muscle fibers from bovine semimembranosus muscle of 41 animals was investigated 3 to 4 h and 3 wk postmortem. Significant relations ( P < 0.05) were found between OCR measurements and Warner–Bratzler shear force measurement. Muscles with high mitochondrial OCR after 3 to 4 h and low nonmitochondrial oxygen consumption gave more tender meat. Tender (22.92 ± 2.2 N/cm 2 ) and tough (72.98 ± 7.2 N/cm 2 ) meat samples (4 samples each), separated based on their OCR measurements, were selected for proteomic studies using mitochondria isolated approximately 2.5 h postmortem. Twenty-six differently expressed proteins ( P < 0.05) were identified in tender meat and 19 in tough meat. In tender meat, the more prevalent antioxidant and chaperon enzymes may reduce reactive oxygen species and prolong oxygen removal by the electron transport system (ETS). Glycolytic, Krebs cycle, and ETS enzymes were also more abundant in tender meat.